Radicalização Islâmica no Norte de Moçambique: O Caso de Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2019)
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui.
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Limits of gender equality: Poor, uneducated Mozambicans less likely to see improvement - Bhoojedhur, Sadhiska; Isbell, Thomas (AFR Barometer, 2019)
Gender equality is enshrined in Mozambique’s Constitution and promoted through its participation in international conventions and treaties as well as its 2004 Family Code, which requires equality in property and family law, including sharing of assets within marriage (International Federation for Human Rights, 2007; UN Women, 2012). During the launch of a National Plan of Action on Women, Peace, and Security in June 2018, the Minister of Gender, Children, and Social Welfare reiterated the government’s commitment to promoting gender equality, emphasizing that equal participation of men and women in all spheres of society is a prerequisite for sustainable development (AllAfrica, 2018). Yet gender disparities are a persistent reality for many women in Mozambique, in forms ranging from child marriage and teen pregnancy to domestic violence and sexual abuse (Cumbe, Materula, Sadler, & Agosta, 2017; Christensen, 2018). According to a United Nations Country Team report (2013), more than half of Mozambican women report having suffered some form of physical, sexual, or psychological violence, and almost three-fourths of girls said they were aware of cases of sexual abuse and harassment in their schools. Mozambique ranks 138th out of 164 countries on the United Nations Development Programme’s (2018) Gender Development Index, and especially in the North and in rural areas, traditional patriarchal values remain strong (Tvedten, 2011). In leadership roles, Mozambican women are better represented than women in many other African countries: 40% of the Mozambican Parliament are women (World Bank, 2018). However, while the Global Gender Gap Report ranked Mozambique No. 1 in Africa in 2008 in terms of economic participation and opportunity, by 2018 the country had dropped to No. 7 (No. 49 in the world) because of setbacks in women’s labour-force participation, particularly in senior and managerial positions (World Economic Forum, 2008, 2018). According to the latest Afrobarometer survey, a majority of Mozambicans think gender equality has been achieved with regard to education, work, and land, and give the government good marks on promoting opportunities for women. However, poor and lesseducated citizens are considerably less likely to perceive progress on gender equality. Moreover, Mozambicans’ support for equality is uneven: While most endorse equality in access to land and political leadership, majorities prioritize men when it comes to getting a job and say families are better off if a woman, rather than a man, takes care of home and children.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; poverty / pobreza

Protecção social e poupança em 10 edicões dos desafios: que tipo de protecção social pode Moçambique desenvolver? - Siúta, Moisés S. (Desafios para Moçambique 2019, 2019)
Que tipo de protecção social poderá Moçambique desenvolver sem poupança interna e profundamente dependente da poupança externa? Esta é a questão principal que este artigo pretende discutir. A discussão é feita em dois sentidos: mostrar a importância da pesquisa dentro da qual a pergunta surgiu e mostrar a relevância da relação que a mesma estabelece entre a poupança e a protecção social. No primeiro sentido, a relevância da pesquisa é demostrada na abordagem das limitações e deficiências do sistema e formas de protecção social vigentes em Moçambique, destacando-se os elementos que podem contribuir para melhorar o sistema de protecção social moçambicano, abordados dentro do trabalho de pesquisa do IESE. Em geral, os resultados da pesquisa apontam como principal deficiência do sistema de protecção social em Moçambique a sua incapacidade de fornecer protecção digna aos cidadãos, que se socorrem das suas diversas formas (e.g.: demográfica ou financeira) e mecanismos de funcionamento (e.g.: familiar, comunitário, financeiro público e privado). No segundo sentido, a importância da pergunta principal do artigo é fundamentada teórica e empiricamente por meio da identificação das relações existentes entre a protecção social e a poupança e da forma como essas relações se manifestam no caso particular em Moçambique. Por exemplo, o artigo discute o quadro teórico de análise do papel da poupança no crescimento e desenvolvimento económico (figura 1) e a forma como este influencia e determina o tipo, as formas e a qualidade da protecção social que Moçambique pode oferecer aos seus cidadãos. Além do quadro teórico, recorrendo a dados empíricos dos países do mundo inteiro, busca-se enquadrar a economia e o sistema de protecção social moçambicano e estabelecer a relação entre o tipo, as formas e a qualidade da protecção social com o nível de poupança, crescimento e desenvolvimento económico.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; poverty / pobreza; social protection / proteção social; ⛔ No DOI found